EFFECT OF NON-PHARMACOLOGICAL INTERVENTIONS ON GLYCEMIC CONTROL FOR GESTATIONAL DIABETES MELLITUS: A SYSTEMATIC REVIEW - Fajriyah, Novita; Andriani, Dewi (jfpublisher, 2022)
Introduction. Gestational Diabetes Mellitus (GDM) is defined as Impaired Glucose Tolerance (IGT) with onset or first recognition during pregnancy. Gestational diabetes mellitus occurs in 2 to 9 percent of all pregnancies and is associated with substantial rates of maternal and perinatal complications. Women with a history of GDM have a sevenfold lifetime risk of developing type 2 diabetes mellitus (T2DM) compared with those with euglycemic pregnancies.A systematic review was conducted to evaluate the evidence from published studies on the effect of non-pharmacological interventions on the health of glycemic control of pregnant women at high risk (gestational diabetes mellitus).Method. The databases used in this systematic review are Scopus, Science Direct, and PubMed. Relevant articles were searched from 27 May to 29 June 2022. The publication year was limited to 2018 – 2022. A total of 20 randomized controlled trials were included that focused on non-pharmacological interventions in GDM women.Results & Analysis. The selected articles show that physical exercise interventions consist of moderate-intensity aerobic and resistance exercise, educational interventions include telemedicine and mobile health (m-health), and dietary nutrition interventions.Discussions. Non-pharmacological interventions can have a good effect on the control of GDM in the treatment of GDM. In general, women with GDM can improve their condition and prevent the risk of complications in childbirth. The physical exercise intervention had a significant beneficial effect on controlling blood glucose levels in GDM women, while other interventions that also had a beneficial effect were education with telemedicine and mobile health media.